Peran Hifz Al-Mal dalam Membentuk Praktik Frugal Living dan Kontribusinya Terhadap Gaya Hidup Berkelanjutan di Kalangan Rumah Tangga Muslim Watampone - Surya Karmila Sari; Hukmiah Husain; Ida Farida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the role of the principle of hifz al-mal in shaping frugal living practices and its contribution to sustainable lifestyles among Muslim households in Watampone. It is motivated by the growing trend of excessive consumption, which negatively impacts both financial stability and the environment. Using a descriptive qualitative approach, data were collected through interviews with ten informants to explore their understanding and daily practices. The findings reveal that most informants perceive hifz al-mal as a religious obligation to protect wealth from wasteful and non-beneficial use. This principle is applied through careful financial management, prioritizing essential needs, and avoiding consumptive behavior. The practice of frugal living is not solely rooted in religious values but is also reinforced by family upbringing and social influences. The contribution to sustainable living is reflected in efforts to conserve energy, water, and other resources. However, most of these actions are driven by a desire for cost efficiency rather than an awareness of environmental impacts, due to limited knowledge about sustainable lifestyles. Awareness of waste management and environmental responsibility also varies among informants. In conclusion, the study finds that hifz al-mal plays a significant role in encouraging frugality that aligns with sustainable living principles. Therefore, comprehensive education is needed to strengthen the connection between Islamic teachings particularly hifz al-mal and environmental sustainability responsibilities.